Low-intensity pulsed ultrasound ameliorates partial infraorbital nerve ligation-induced trigeminal neuropathic pain through inhibiting Schwann cell Pannexin 1 channel - Liu, Yao; Han, Xue; Zhang, Weijie; Pei, Qingguo; Xu, Shuyu; Wang, Haicheng (Frontiers in Immunology, 2026)
BackgroundNeuroinflammation significantly contributes to trigeminal neuropathic pain (TNP). Low-intensity pulsed ultrasound (LIPUS) showed anti-inflammatory function in several diseases. It is still unknown that whether LIPUS show its analgesic effect against TNP. This study investigated how LIPUS alleviates pain in mice with TNP from partial infraorbital nerve ligation (pIONL).Materials and MethodsICR mice, 7–11 weeks, were prepared. von Frey test was used to analyze all the nocifensive behavior score. RNA-sequencing was performed on the infraorbital nerve (ION) three days post-pIONL and on 24-hour cultured Schwann cells to identify inflammation-related genes and pathways. RT-qPCR, western blotting, immunofluorescent staining was used to analyze the expressions of Pannexin 1 channel and pro-inflammatory cytokines in vivo and in vitro studies.ResultspIONL induced persistent neuroinflammatory responses and mechanical allodynia, which were ameliorated by LIPUS treatment. Panx 1 was highly expressed after pIONL., LIPUS treatment inhibited pIONL-induced neuroinflammation in ION, trigeminal ganglion, and spinal cord tissue. Inhibition of Panx 1 via siRNA significantly attenuated the mechanical allodynia. Several cytokines were inhibited by Panx 1-siRNA, both Panx 1-siRNA and LIPUS treatment suppressed several cytokines. Next, we cultured Schwann cells with TNF-α (200ng/ml). We found LIPUS effectively downregulated the expression of Panx 1 and pro-inflammatory cytokines in Vitro. Intra-ION injection of BzATP induced TNP, which was ameliorated by LIPUS along with downregulation of Panx 1 and pro-inflammatory cytokines,. RNA-sequencing analysis revealed that LIPUS downregulates pathways related to inflammation, ion channels, and metabolism in Schwann cells.ConclusionsThis study demonstrates that LIPUS exerts an analgesic effect by targeting Panx1 in Schwann cells of the peripheral nervous system, thereby ameliorating neuroinflammation and providing sustained relief from TNP.